Biotechnology for Food Future - Su, Lin.; Koorevaar, Frank; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
Biotechnology for Food Future aims to be at the forefront of food biotechnology, focusing on the future of food. It seeks to publish cutting-edge research and innovative solutions that address the global challenges of food production, safety, and sustainability. The journal will serve as a platform for scientists, researchers, and industry professionals. The journal covers a broad range of topics related to the future of food, including but not limited to: Advanced Genetic Engineering: Innovations in genetic modification to enhance crop yields, nutritional value, and resistance to environmental stresses, including boosting soil health. Next-Generation Functional Foods: Development of foods with additional health benefits, such as probiotics, prebiotics, and nutraceuticals. This includes research on food microbiomes for health. 3D Food Printing and other technological disruptions: New biotechnologies for customized food products with specific nutritional profiles, with impact on personalized nutrition and food design. Sustainable Food Production: Techniques and technologies aimed at reducing the environmental impact of food production, including alternative protein sources like lab-grown meat and plant-based proteins. Food Safety and Quality: Modern molecular, metabolic, and biochemical approaches to ensure the safety and quality of food products, including detection and prevention of foodborne pathogens. Biotechnological Food Processing: Use of enzymatic and microbial processes to improve food processing and explore new methods of preservation. Food Waste Management: Innovative methods to convert food waste into valuable bioproducts, contributing to a circular economy and enhance food waste remediation. Bio-based Smart Packaging: Use of bio-based sustainable materials for developments in enhancing food safety, extending shelf life, and reducing waste. Policy, public engagement, and society: Studies about effective food biotechnology policy bridging scientific innovation and societal values, ensuring transparency and trust, and insights on public understanding and approaches fostering informed choices and acceptance of food innovations in a rapidly evolving world. The journal also welcomes interdisciplinary research that bridges the gap between food biotechnology and other fields such as nutrition, agriculture, and environmental science. By fostering collaboration and knowledge exchange, the journal aims to drive the development of sustainable and innovative food solutions for the future. Researchers, practitioners, and policymakers in the fields of food science, biotechnology, agriculture, and nutrition will find the journal to be an invaluable resource for staying updated on the latest trends and breakthroughs in food biotechnology. Biotechnology for Food Future will be a new addition to the Biotechnology family of journals. .
Keywords: Life sciences; Biology; Food science; Life Sciences; Biological Sciences; Food Science